2023
DOI: 10.3390/foods12152854
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects Mediated by Enteromorpha prolifera Polysaccharide and Its Zn(II) Complex on Hypoglycemic Activity in High-Sugar High-Fat Diet-Fed Mice

Abstract: In order to investigate and develop functional foods of marine origin with hypoglycemic activity, Enteromorpha prolifera polysaccharide–Zn(II) (EZ) complex was first prepared by marine resourced E. prolifera polysaccharide (EP) and ZnSO4 and their anti-diabetes activities against high-sugar and high-fat-induced diabetic mice were evaluated. The detailed structural characterization of EZ was elucidated by UV-Vis spectroscopy, infrared spectroscopy, and monosaccharide composition determination. The pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…We found that Firmicutes and Bacteroidota were the major phyla among the three groups, which was in line with previous findings [19,43,44]. In addition, increasing abundances of Clostridiaceae (Clostridium_sensu_stricto_1), f_Peptostreptococcaceae, f_Muribaculaceae, Terrisporobacter, Subdoligranulum and Intestinibacter were found in fecal samples, with the addition of different types and forms of Zn sources, which was found previously [44,45]. The potential pathogenic bacteria Clostridium_sensu_stricto_1, belonging to the Clostridiaceae family, was reported to produce SCFAs and promote intestinal mucus barrier adhesion to pathogens [46].…”
Section: Discussionsupporting
confidence: 92%
“…We found that Firmicutes and Bacteroidota were the major phyla among the three groups, which was in line with previous findings [19,43,44]. In addition, increasing abundances of Clostridiaceae (Clostridium_sensu_stricto_1), f_Peptostreptococcaceae, f_Muribaculaceae, Terrisporobacter, Subdoligranulum and Intestinibacter were found in fecal samples, with the addition of different types and forms of Zn sources, which was found previously [44,45]. The potential pathogenic bacteria Clostridium_sensu_stricto_1, belonging to the Clostridiaceae family, was reported to produce SCFAs and promote intestinal mucus barrier adhesion to pathogens [46].…”
Section: Discussionsupporting
confidence: 92%